PENGARUH KUALITAS PRODUK LABEL HALAL DAN POTONGAN HARGA PRODUK KOSMETIK ORIFLAME TERHADAP MINAT BELI MASYARAKAT KOTA SAMARINDA - Rizka Handayani (University of Widya Gama Mahakam Samarinda, 2021)
The purpose of this study was to determine the effect and relationship of product quality, halal labels and discounts on Oriflame cosmetic products on the buying interest of the people of Samarinda. This research method is descriptive quantitative with Multiple Linear Regression analysis, and uses statistical analysis tools with the help of SPSS version 26 computer program to determine the effect and relationship of each variable. From the results of the analysis, it is known that the correlation coefficient between product quality, halal labels and price discounts has a strong relationship of 0.730. The results of statistical tests state that jointly product quality, halal labels and price discounts affect buying interest with a Ftable value of 30.860 > 2.72 and a significant value of 0.000 < 0.05. The results of this study indicate that 1) Product quality has a significant effect on buying interest; 2) Halal label has no significant effect on buying interest; 3) Price discounts have no significant effect on buying interest